PENGARUH IMPORTANCE TO CAREER, FAMILY SUPPORT, EXPERIENCE OF FACULTY TERHADAP INTENTION TO PARTICIPATE IN STUDY ABROAD , TELAAH PADA PARA MAHASISWA UNIVERSITAS SWASTA, TANGERANG, BANTEN, INDONESIA - boby arinto; Nosica Rizkalla (Universitas Multimedia Nusantara, 2019)
The demand for internationalization activities of higher education has increased for years. More international students are interested in joining the program. For universities, the internationalization program has a significant impact on improving accreditation. Meanwhile, the Study Abroad Program, as part of internationalization, plays a vital role for students because it has a good effect for the students to get career objectives after they graduate from university. The problem is the ratio of the number of participants of the Study Abroad program in Indonesia is still relatively low compared to other countries in the ASEAN level. Therefore, the problem and how to overcome it is an essential topic in this research. In this study, we use a theoretical background from the Theory of Planned Behavior (TPB), which predicts intentions to study abroad. Respondents in this study were the students of Multimedia Nusantara University, Tangerang, Indonesia. The result is the importance of a career, the experience of professor in Study Program and family supports have the positive intention to participate in study abroad.